APLIKASI SISTEM PEMBELIAN PADA PT. HINGS SUBUR MAKMUR - Gunawan Putrodjojo; Sugesti Sugesti; Helen Tan (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
This paper is the outcome of reserch at PT. Hings Subur Makmur. Buying System at PT. Hings Subur Makmur still uses manually system, so frequent mistake in the transaction, then need to build a buying system in computerized. The system application made is application the buying system useful to reduce the mistake for this happened in the process of purchasing and to ease in doing the purchase process effective and afficient. In the application system there is report pertaining to the buying system. The methods used in the buying system it uses Unifield Modelling Language (UML), to be made use of programming Visual Basic.Net and use SQL Server 2008 as database. A form report using Crystal Report. Operation System use Microsoft Windows7. Design of the new system generates an application program that has been integrated with each other and make it easier to access the information needed and help the company overseeing the purchasing system.